2021
DOI: 10.1093/ehjcr/ytab504
|View full text |Cite
|
Sign up to set email alerts
|

POEMS syndrome causing left ventricular hypertrophy, myocardial dysfunction, and pericardial effusion: a case report

Abstract: Background POEMS syndrome (polyneuropathy, organomegaly, endocrinopathy, M-protein, skin changes) is a paraneoplastic syndrome caused by a plasma cell proliferative disorder. Characteristics of POEMS syndrome include elevated pro-inflammatory and angiogenic cytokine levels that lead to multi-organ dysfunction. Patients have a variety of initial symptoms, but cardiac involvement is not common. Case summary We report a case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The diagnosis of POEMS syndrome poses a challenge due to its rare occurrence and complex clinical symptoms.And its diagnostic criteria are based on the current Dispenzieri diagnosis. [4] .The main manifestation of POEMS syndrome is peripheral neuropathy, which may be accompanied by multiple plasma cavities, sclerotic bone damage, and organomegaly [4] .However, POEMS syndrome may also be characterized by a variety of atypical presentations, among which plasmapheresis is commonly reported [5][6][7][8][9] .Wang W [7] reported a 69-year-old woman whose condition mirrored our patient's, initially misdiagnosed as tuberculous peritonitis because of abdominal swelling and previous tuberculosis exposure. After the anti-tuberculosis therapy proved ineffective, further detailed investigations ultimately con rmed a diagnosis of POEMS syndrome.She was treated with a combination of lenalidomide (25 mg/day) and dexamethasone (40 mg/week), leading to signi cant improvement and her subsequent discharge.A retrospective study found that of 282 cases of POEMS syndrome, 40.1% presented with respiratory symptoms, of which 56.4% presented with pleural effusion [10] .Therefore, it is not uncommon for patients with POEMS syndrome to present with pleural effusions.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of POEMS syndrome poses a challenge due to its rare occurrence and complex clinical symptoms.And its diagnostic criteria are based on the current Dispenzieri diagnosis. [4] .The main manifestation of POEMS syndrome is peripheral neuropathy, which may be accompanied by multiple plasma cavities, sclerotic bone damage, and organomegaly [4] .However, POEMS syndrome may also be characterized by a variety of atypical presentations, among which plasmapheresis is commonly reported [5][6][7][8][9] .Wang W [7] reported a 69-year-old woman whose condition mirrored our patient's, initially misdiagnosed as tuberculous peritonitis because of abdominal swelling and previous tuberculosis exposure. After the anti-tuberculosis therapy proved ineffective, further detailed investigations ultimately con rmed a diagnosis of POEMS syndrome.She was treated with a combination of lenalidomide (25 mg/day) and dexamethasone (40 mg/week), leading to signi cant improvement and her subsequent discharge.A retrospective study found that of 282 cases of POEMS syndrome, 40.1% presented with respiratory symptoms, of which 56.4% presented with pleural effusion [10] .Therefore, it is not uncommon for patients with POEMS syndrome to present with pleural effusions.…”
Section: Discussionmentioning
confidence: 99%